Consciousness Without Content: A Look at Evidence and Prospects - Srinivasan, Narayanan (Frontiers in Psychology, 2020)
Many traditions in the east have proposed that consciousness without content is possible and could be achieved with mental training. However, it is not clear whether such a state is possible given that intentionality is a critical property of mentality and consciousness in many theories of consciousness. A prominent recent attempt to account for such states of “minimal phenomenal experience” is the ARAS model, which proposes a specific type of content-based representation to address such a state. Consciousness without content can also be understood by studying related or similar states of minimal phenomenal experience and this paper discusses such findings from such states including dreamless sleep experience and their implications. One way to argue for the need for proposing consciousness without content is to locate a property of consciousness that would necessitate postulating it. A continuous state of consciousness without content may be needed to understand continuity of conscious experience. Finally I will discuss the implications of consciousness without content for current theories of consciousness.